Shaping entrepreneurial ecosystems through knowledge and technology transfer: Local and non-local dynamics in entrepreneurial ecosystem evolution (2024)
This doctoral dissertation contributes to the understanding of the evolution of entrepreneurial ecosystems by exploring how knowledge transfers, social capital, and both internal and external actors shape ecosystem structure. Using a qualitative approach, Chapter One and Chapter Two examine the ecosystems of Bogotá and São Paulo to uncover the role of knowledge and technology transfers in shaping ecosystem structure through the lens of social capital and orchestration theories. Chapter One analyzes how relational and cognitive conditions within the network facilitate knowledge and technology transfers, influencing the ecosystem’s structure. Chapter Two builds on these insights by exploring how anchor organizations shape the ecosystem—not by directly altering structural elements, but through orchestration strategies that create the relational and cognitive conditions necessary for effective knowledge transfers, ultimately shaping the structure. Chapter Three shifts focus to non-local factors and employs a quantitative approach to analyze the role of diaspora communities from seven Balkan and seven Latin American countries for the development of the entrepreneurial ecosystems in the respective countries of origin. The findings indicate that migration and remittances, particularly in the Balkans, promote "brain circulation" and opportunity-driven entrepreneurship in the entrepreneurial ecosystem of the countries of origin, while the impact of Latin American diasporas on local ecosystems is less pronounced. Together, the chapters of this doctoral dissertation uncover how local and non-local actors shape entrepreneurial ecosystems through knowledge and technology transfer.